The numerical–experimental scheme for the analysis of temperature field in a pad-disc braking system of a railway vehicle at single braking. (July 2016) - Grzes, P.; Oliferuk, W.; Adamowicz, A.; Kochanowski, K.; Wasilewski, P.; Yevtushenko, A.A.
Abstract: A single braking process based on actual dimensions of the sliding components of the railway braking system, operating parameters, and properties of materials is analysed. The cast-iron brake disc combined with the pads made of the advanced organic composite material were examined. First, the properties of the friction material using the pulsed infrared (IR) thermography were determined. In the next step, the numerical FE solution to the thermal problem of friction for the pad-disc braking system was obtained. The calculated changes in transient temperature fields of the pad and the disc during braking were presented. Then the calculated numerically maximum temperatures for the series of different parameters, mass per wheel, initial velocity, coefficient of friction, applied load were compared with the corresponding measured values using thermocouples embedded in the disc. Based on the presented outcomes, the proposed numerical–experimental scheme for the analysis of temperature in the railway braking system was verified.